2004
DOI: 10.1111/j.1474-919x.2004.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climate change on birds

Abstract: Weather is of major importance for the population dynamics of birds, but the implications of climate change have only recently begun to be addressed. There is already compelling evidence that birds have been affected by recent climate changes. This review suggests that although there is a substantial body of evidence for changes in the phenology of birds, particularly of the timing of migration and of nesting, the consequences of these responses for a species' population dynamics is still an area requiring in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
351
4
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(378 citation statements)
references
References 67 publications
8
351
4
15
Order By: Relevance
“…In recent years, evidence has mounted about its impacts on different groups of species and stages of a species lifecycle (Hughes, 2000;Parmesan, 2006). Especially for birds (Crick, 2004;Chambers et al, 2005;Leech and Crick, 2007;Wormworth and Mallon, 2007), climate change has been shown to induce poleward (Hitch and Leberg, 2007) and upward shifts of the distributional ranges (Pounds et al, 1999), to alter the timing of major seasonal events such as migration (Jenni and Kéry, 2003;Jonzen et al, 2006;Gordo, 2007) or egg laying (Crick and Sparks, 1999;Torti and Dunn, 2005;Both and te Marvelde, 2007) and to influence survival and productivity and hence, population dynamics (Sanz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, evidence has mounted about its impacts on different groups of species and stages of a species lifecycle (Hughes, 2000;Parmesan, 2006). Especially for birds (Crick, 2004;Chambers et al, 2005;Leech and Crick, 2007;Wormworth and Mallon, 2007), climate change has been shown to induce poleward (Hitch and Leberg, 2007) and upward shifts of the distributional ranges (Pounds et al, 1999), to alter the timing of major seasonal events such as migration (Jenni and Kéry, 2003;Jonzen et al, 2006;Gordo, 2007) or egg laying (Crick and Sparks, 1999;Torti and Dunn, 2005;Both and te Marvelde, 2007) and to influence survival and productivity and hence, population dynamics (Sanz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…M. persicus breeds in these areas, whilst M. apiaster only passes through during its spring arrives about a fortnight earlier than M. apiaster, and these variations are probably due to fluctuations in the weather conditions (Crick, 2004;Yosef et al, 2006;DeCndido et al, 2010;Sapir et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Cramp (1985) reported that, especially in cold, dull weather or after rain, flocks of M. apiaster (up to c. 250) arrive at apiaries in the morning and evening. The weather may affect the metabolic rates of birds, causing indirect and direct effects on their behaviour (Crick, 2004), and during their migratory journeys, individual birds have to decide on a daily basis when to leave their resting sites based on the local meteorological conditions and their physiological condition (Sapier et al, 2011).…”
Section: Fig 3bmentioning
confidence: 99%
“…Typically, spatial studies on the impact of climate change have focused on the prediction of range contractions and range shifts but not on the changes of population size. This is surprising, because many bird species may exhibit population change due to the impact of climate on survival rate and breeding success, independent of a possible change of their geographic distribution (Crick 2004). Following this argument, climate change might have a more immediate influence on a bird species' abundance than on its incidence.…”
Section: Introductionmentioning
confidence: 95%